PENOMENA PERKAWINAN PAMELIN LUH DALAM PEMBENTUKAN PENDIDIKAN KARAKTER UMAT HINDU DI DESA BEBETIN BULELENG - I Nyoman Temon Astawa (GUNA WIDYA: JURNAL PENDIDIKAN HINDU, 2020)
Character education in the family is strongly influenced by the family's existence of the child. A happy family can be determined from the initial formation of the family. The formation of a family certainly starts from the marriage process. One form of marriage that is carried out is the tradition of pamel luh marriage.According to the Pamelin marriage ceremony in Pakraman Bebetin Village, this social function was clearly visible from the beginning of the marriage plan. In marriages that are carried out by memadik (ngidih, propose), then there is contact and communication that has been done when the male family conveys the intention of his arrival will propose to the daughter of the woman. Social interactions between the male family and the female family have occurred during the work (mekruna). If there is certainty and agreement on a good day in the implementation of the marriage ceremony then in this connection the more visible sense of togetherness in social life in the form of mutual cooperation in the banjar pakraman or Bebetin community. The sense of solitude of the Bebetin Village community is quite high. This can be seen if there are members of the community (banjar) who will carry out a ceremony or yajña both in a state of joy and sorrow without being invited as long as they hear it must come and help in the form of material and energy.